Waste Collection, Sorting and Storage and Food Waste Management on Disney Cruise Line Ships - Manoiu, Valentina-Mariana (European Scientific Journal, ESJ, 2018)
This paper presents the waste collection, sorting and storage on Disney Cruise Line (DCL) company ships, as well as in-house food waste management procedures. In a previous paper, we singled out the DCL company’s environmental policies, as well as the cruise itinerary waste management plans for the enterprise’s ships. The paper analyses the in-house environmental personnel’s activity, the company’s internal regulations, and relevant data and field observations collected by the environmental protection staff, and presents data on the collection, sorting and storage of the waste generated by DCL cruise ships, and details food waste processing and discharge methods. The paper confirms the DCL company’s intention to minimize its fleet’s environmental impact by implementing the appropriate waste collection, sorting and storage methods, as well as by reducing food waste amounts and ensuring an efficient food waste management. In 2013, DCL was declared the most environmentally-responsible cruise line, according to the Cruise Industry Environmental Report Card. All crew members are charged with complying with environmental requirements and DCL’s environmental policy. Both crew members and customers must pay attention to practices that can accidentally result in food waste pollution. Food waste collection and the prevention of improper overboard spillage of waste are carefully supervised by everyone on board. The DCL company makes constant efforts to reduce food waste amounts and associated risks to a minimum across its commercial fleet. This entails using proper waste storage and disposal procedures, as well as planning the supply of raw materials and food ingredients